A Review on Gold Nanoclusters for Cancer Phototherapy - Yang, Zhuoren; Yang, Xiebingqing; Guo, Yahui; Kawasaki, Hideya (ACS applied bio materials, 2023)
Cancer phototherapy, including photodynamic therapy (PDT) and photothermal therapy (PTT), has been extensively studied in recent years because of its noninvasive properties, high efficiency, improved selectivity, and reduced side effects. Gold nanoclusters (AuNCs) have the advantages of high biocompatibility, high biosafety, excellent photoresponse, and high tumor penetration ability. This review analyzes the use of AuNCs in tumor phototherapy in recent years from three aspects, namely, AuNCs in PDT, AuNCs in PTT, and AuNCs in combination therapy, and presents the high potential of AuNCs in cancer phototherapy. This review aims to provide readers with the unique advantages, diversified application approaches, and bright application prospects of AuNCs in phototherapy and to provide insights into strategies for applying AuNCs to tumor phototherapy.Cancer phototherapy, including photodynamic therapy (PDT) and photothermal therapy (PTT), has been extensively studied in recent years because of its noninvasive properties, high efficiency, improved selectivity, and reduced side effects. Gold nanoclusters (AuNCs) have the advantages of high biocompatibility, high biosafety, excellent photoresponse, and high tumor penetration ability. This review analyzes the use of AuNCs in tumor phototherapy in recent years from three aspects, namely, AuNCs in PDT, AuNCs in PTT, and AuNCs in combination therapy, and presents the high potential of AuNCs in cancer phototherapy. This review aims to provide readers with the unique advantages, diversified application approaches, and bright application prospects of AuNCs in phototherapy and to provide insights into strategies for applying AuNCs to tumor phototherapy.